Does Entrepreneurial Self-efficacy Matter on Professional’s Entrepreneurial Intention? - Sunanto Sunanto; Hamdy Hady; Jan Horas V Purba (Asean International Journal of Business, 2023)
This study aims to investigate determinants of entrepreneurial intention (EI) consisting of entrepreneurial education (EE), entrepreneurial self-efficacy (ESE) and entrepreneurial attitude (EA) of professional pharmacists within Greater Jakarta of Indonesia by referring to the theory of planned behaviour (TPB). Research on EI and its determinants in specific business fields with pharmacists as research subjects have not been widely revealed. This investigation uses quantitative approach with a cross-sectional survey model. The population of this study is all pharmacists registered within the Indonesian Pharmacists Association (IAI), and we obtained 391 sample based on the Slovin formula (error 5%). This research used a proportional random sampling and was analyzed undergoing Structural Equation Modelling (SEM-Lisrel). The results showed significant positive impact of EE, ESE, and EA on EI. Likewise, EE, ESE has a significant positive effect on EA. Therefore, EA can play as mediator (partial mediating) to the relationship of ESE and EI but not so with EE and EI. This study succeeded in explaining the role of ESE as a dominant factor in informing EI. The paper provides evidence and these findings are of interest to business, academia and policy makers.